Variations in Soil C, N, P Stocks and Stoichiometry With Soil Depth and Forest Types in Qilian Mountains of Northwest China - Rahman, Mujibur; Wang, Yanhui; Zhang, Kebin; Ahmad, Bilal; Ali, Ashfaq; Ahamd, Adnan; Muhammad, Dost; Afzaal, Muhammad; Zhang, Ziyou; Bohnett, Eve (Frontiers in Environmental Science, 2022)
Forests ecosystem plays a significant role in supplying multiple services given the unique properties of forest soils, in which the elements of C, N, and P are essential to support soil fertility and site productivity. However, soil properties at different soil depths between plantation forests (PF) and natural forests (NF) have not been well quantified. Therefore, the current study was carried out in the Qilian Mountains of northwest China to determine the difference between PF and NF in the soil properties, both physical (e.g., bulk density, BD) and chemical (e.g., pH value, the contents, stocks, and stoichiometry of soil organic carbon (SOC), total N (TN), and total P (TP). Research analyzed soil samples at different depths (0-20, 20-40, 40-60, 60-80, and 80-100 cm). The results showed that the soils’ pH values and BD were significantly higher (p≤0.05) in PF than in NF and increased with soil depth. The contents of SOC, TN, and TP decreased considerably with soil depth and then stabilized at the soil depth of 80-100 cm. The NF showed significantly higher (p≤0.05) SOC, TN, and TP contents than PF, confirming that the soil quality of PF had not fully recovered yet. The stocks of SOC and TN quickly decreased with soil depth up to 40-60 cm and stabilized gradually. Additionally, the soil stoichiometry of C:P and N:P decreased significantly with rising soil depth, while the C:N ratio remained unchanged. The N:P and C:P ratios were lower in PF than in NF, while the C:N ratio was higher in PF than in NF. In conclusion, results show that the soils of NF present significantly higher stocks of SOC and TN but lower (or nearly equal) TP stocks than PF (under the same age group and tree species composition). These results imply that maintaining NF and avoiding their replacement by PF can help keep higher soil quality and related ecosystem services.